2017
DOI: 10.1016/j.apjtm.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Advances in research on Zika virus

Abstract: Zika virus (ZIKV) is rapidly spreading across the America and its devastating outcomes for pregnant women and infants have driven this previously ignored pathogen into the limelight. Clinical manifestations are fever, joint pain or rash and conjunctivitis. Emergence of ZIKV started with a first outbreak in the Pacific area in 2007, a second large outbreak occurred in the Pacific in 2013/2014 and subsequently the virus spread in other Pacific islands. Threat of explosive global pandemic and severe clinical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 94 publications
(107 reference statements)
0
32
0
4
Order By: Relevance
“…Studies have suggested that the Zika virus acts through neurotropism, so that it affects the cortical progenitor cells of the central nervous system when it crosses the placental barrier, thereby inducing structural and functional lesions and cell death. This virus may also trigger an inflammatory cascade, with a release of cytokines as a response to viral damage, thus leading to aberrant embryogenesis (Ali, Wahid, Rafique, & Idrees, ; Eickmann et al, ; Schuler‐Faccini et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that the Zika virus acts through neurotropism, so that it affects the cortical progenitor cells of the central nervous system when it crosses the placental barrier, thereby inducing structural and functional lesions and cell death. This virus may also trigger an inflammatory cascade, with a release of cytokines as a response to viral damage, thus leading to aberrant embryogenesis (Ali, Wahid, Rafique, & Idrees, ; Eickmann et al, ; Schuler‐Faccini et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Posteriormente, em 1954, foi reportada a infecção em humanos na Nigéria e, ao longo das décadas de 1950 e 1960, estudos sorológicos sugeriram tratar-se de uma endemia desse flavivírus em toda a África e em vários países do continente asiático (BRITT, 2018;WIKAN et al, 2016). Em 2007, foi relatado o primeiro surto de infecção pelo vírus Zika na ilha de Yap, nos Estados Federados da Micronésia, seguido por vários surtos em ilhas do Pacífico (ALI et al, 2017;FARIA et al, 2016). Nessas ilhas, 73% da população apresentava sintomas da infecção por Zika, sendo 49 casos efetivamente confirmados (ALI et al, 2017).…”
Section: Histórico Distribuição Geográfica E Epidemiologia Do Zikvunclassified
“…Em 2007, foi relatado o primeiro surto de infecção pelo vírus Zika na ilha de Yap, nos Estados Federados da Micronésia, seguido por vários surtos em ilhas do Pacífico (ALI et al, 2017;FARIA et al, 2016). Nessas ilhas, 73% da população apresentava sintomas da infecção por Zika, sendo 49 casos efetivamente confirmados (ALI et al, 2017).…”
Section: Histórico Distribuição Geográfica E Epidemiologia Do Zikvunclassified
See 2 more Smart Citations